2003
DOI: 10.1038/sj.leu.2403083
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of natural killer (NK) and natural killer-like T (NKT)-cell populations derived from patients with B-chronic lymphocytic leukemia (B-CLL): a potential source for cellular immunotherapy

Abstract: B-cell chronic lymphocytic leukemia (B-CLL) is the most common leukemia in the Western world. It is currently an incurable disease, making new treatment options such as immunotherapy desirable. Monoclonal antibodies (Mabs) to surface antigens of the tumor cell is one option. Administration of cytotoxic cells such as natural killer (NK) and natural killerlike T (NKT) cells expanded in vitro might be a useful treatment modality alone or in combination with MAbs. A limiting step in the development of successful c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 34 publications
1
62
0
2
Order By: Relevance
“…15,16 This hypothesis was suggested by the restoration of their functional activity after interferon (IFN)-a and/or interleukin (IL)-2 treatment. 17,18 We conducted the first extensive characterization of the phenotypic and cytotoxic qualities of NK cells from CLL patients and compared them with those of healthy subjects. Our data reveal that NK cells from these patients have the major phenotypic features of competent NK cells and are able to function effectively.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 This hypothesis was suggested by the restoration of their functional activity after interferon (IFN)-a and/or interleukin (IL)-2 treatment. 17,18 We conducted the first extensive characterization of the phenotypic and cytotoxic qualities of NK cells from CLL patients and compared them with those of healthy subjects. Our data reveal that NK cells from these patients have the major phenotypic features of competent NK cells and are able to function effectively.…”
Section: Introductionmentioning
confidence: 99%
“…In CLL patients, high burden of malignant B cells in peripheral blood naturally reduces NK cell proportion and negatively affects the natural and antibody-dependent cytotoxicity of the latter. 3,12 Laprevotte et al reported the median NK:B cells ratio as 0.02:1 in CLL patients and further showed that IL-15 could expand patients' NK cells, which in turn elevated CLL cell depletion by anti-CD20 antibodies (Rituximab and GA101). 12 To check whether increasing NK: B cells ratio also enhances the killing activity of the immunoligand, we purified NK cells from both patients 3 and 4 and incubated with purified CLL cells in autologous setting.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Ex vivo expansion of NK and NKT cells from healthy donors and CLL patients have shown exciting results, where Guven et al reported even better expansion rates for functionally active NK cells from CLL patients despite initial low numbers. 3,48 However, possible side effects of immunoligand-associated NK cell activation in patients such as autoimmune reactions toward healthy B cells should be considered. Limitations of autologous and allogeneic NK cell infusions have been discussed elsewhere 49 and must be pointed out in the context of adoptive transfer of NK cells with immunoligand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations